'Being small is not a fault': Making sense of the newer generation of German‐language university presses. (October 2016) - Bargheer, Margo; Pabst, Jutta
Abstract : Key points There are 33 university presses in Germany, most of them part of the working group of German‐language university presses, AG Universitätsverlage . Göttingen University Press was formed in the late 1990s as an open access service for the university's scholars. A publishing house within the academic network is able to be more responsive to the needs of its institution and scholars than an external publisher solely relying on revenues. Taking control of publishing helps academia ensure that results will be disseminated in a way most beneficial to itself and society.